CONNECTION OF ADDITIONAL PULSAR EMISSION COMPONENTS IN THE CRAB WITH THE RESONANCE REFLECTION FROM A NEUTRON STAR - Kontorovich, V. M.; Spevak, I. S.; Gavrikov, V. K. (Видавничий дім «Академперіодика», 2018)
PACS numbers: 97.60.Jd;97.60.Gb; 52.38.BvPurpose: The subject of the paper is discussion of reflected radiation from the neutron star surface. Such radiation, as was shown earlier by S. V. Trofymenko and one of the authors, occurs when reflects the radiation of relativistic positrons flying from the magnetosphere to a star in the accelerating electric field of the polar gap. This gave an explanation of both the interpulse shift in the Crab pulsar (mirror reflection in an inclined magnetic field) and the appearance of additional HF components (diffraction on the periodic structure excited by the incident radiation) discovered by Moffett and Hankins. The aim of the paper is to study the effect on the HF components of a resonance with a surface electromagnetic wave.Design/methodology/approach: Since the HF components occur at the same frequencies as the interpulse shift, we believe that they are a consequence of the same physical process. Such a process is the reflection from the surface of a neutron star of the radiation of the return positrons. The appearance of HF components is considered as a manifestation of stimulated scattering by surface waves. For comparison, the data of laboratory experiments on the diffraction of laser radiation on a metal diffraction grating are presented. They demonstrate the appearance of a bright near-surface wave under resonance conditions, which can serve as an analog of the HF component in the Crab pulsar.Findings: In the formation of HF components, such phenomena as Wood’s anomalies are significant, leading to considerable essential increase of the increment of stimulated scattering at the resonance with the surface electromagnetic wave. The surface wave excited with the resonance leads to reflected Raman scattering of higher frequencies of the continuous spectrum of the incident radiation.Conclusions: The radiation of a pulsar is determined, among others, by the reflecting properties of the surface of the neutron star, i.e. its conductivity (surface impedance). The resonance substantially reduces the stimulated scattering threshold. The continuous spectrum of the radiation incident on the surface provides a large width of the HF-components.Key words: neutron star, pulsar, interim pulse, HF components, reflection, stimulated Raman scattering, diffraction, Wood anomaliesManuscript submitted 16.07.2018Radio phys. radio astron. 2018, 23(3): 166-175 REFERENCES1. SMITH, F. G., 1977. Pulsars. Cambridge, New York: Cambridge University Press.2. LIPUNOV, V. M., 1987. Astrophysics of neutron stars. Moscow, Russia: Nauka Publ. (in Russian).3. KONTOROVICH, V. M., 2016. Nonlinear reflection from the surface of a neutron stars and and features of radio emission from the pulsar in the Crab nebula. Low. Temp. Phys. vol. 42, is. 8, pp. 672–678. DOI: https://doi.org/10.1063/1.49614884. BESKIN, V. S., 2010. MHD Flows in Compact Astrophysical Objects. Berlin, Heidelberg: Springer. DOI: https://doi.org/10.1007/978-3-642-01290-75. HAENSEL, P., POTEKHIN, A. YU. and YAKOVLEV, D. G., 2007. Neutron Stars 1. Equation of State and Structure. New York: Springer-Verlag. DOI: https://doi.org/10.1007/978-0-387-47301-76. POTEKHIN, A. Yu., 2010. The physics of neutron stars. Phys. Usp. vol. 180, no. 12, pp. 1235–1256. DOI: https://doi.org/10.3367/UFNe.0180.201012c.12797. KONTOROVICH, V. M. and TROFYMENKO, S. V, 2017. On the Mystery of the Interpulse Shift in the Crab Pulsar. J. Phys. Sci. Appl. vol. 7, no. 4, p. 11–28.8. MOFFETT, D. and HANKINS, T. 1996. Multifrequency radio observations of the Crab pulsar. Astrophys. J. vol. 468, pp. 779–783 DOI: https://doi.org/10.1086/1777349. HANKINS, T. H., JONES, G. and EILEK, J. A. 2015. The crab pulsar at centimeter wavelengths: I. Ensemble characteristics. Astrophys. J. vol. 802, no. 2, id. 130. DOI: https://doi.org/10.1088/0004-637X/802/2/13010. EILEK, J. and HANKINS, T. 2016. Radio emission physics in the Crab pulsar. J. Plasma Phys. vol. 82, no. 3, id. 635820302. DOI: https://doi.org/10.1017/S002237781600043X11. PETROVA, S. A., 2010. The Mechanism of Component Formation out of the Main Pulse of a Radio Pulsar. II. The Interpulse. Radio Phys. Radio Astron. vol. 1, no. 1, pp. 27–35. DOI: https://doi.org/10.1615/RadioPhysicsRadioAstronomy.v1.i1.4012. MANDELSHTAM, L. I., 1913. On roughness of free surface of liquid. Ann. Phys. vol. 41, no. 8, pp. 609–624.13. ANDRONOV, A. A. and LEONTOVICH, M. A., 1926. To the theory of molecular light scattering on liquid surface. Z. Phys. vol. 38, pp. 485–501. DOI: https://doi.org/10.1007/BF0139716714. GAVRIKOV, V. K., KATS, A. V. and KONTOROVICH, V. M., 1969. Forced scattering on surface waves. Sov. Phys. Dokl. vol. 14, pp. 564–566.15. KATS, A. V. and MASLOV, V. V., 1972. Stimulated Scattering of Electromagnetic Waves from a Highly Conducting Surface. Sov. Phys. JETP. vol. 35, no. 2, pp. 264–268.16. LANDAU, L. D. and LIFSHITZ E. M., 1960. Electrodynamics of Continuous Media. Oxford: Pergamon Press.17. WOOD, R. W., 1935. Anomalous Diffraction Gratings. Phys. Rev. vol. 48, pp. 928–936. DOI: 10.1103/Phys-Rev.48.92818. RAYLEIGH, L., 1907. On the dynamical theory of gratings. Proc. R. Soc. London, Ser. A. vol. 79, no. 532, pp. 399–416. DOI: https://doi.org/10.1098/rspa.1907.005119. AGRANOVICH, V. M. and MILLS, D. L., (eds.), 1982. Surface Polaritons: Electromagnetic Waves at Surface and Interface. Amsterdam: North Holland.20. KONTOROVICH, V. M. and Trofymenko, S. V., 2017. Reflection of positron radiation from star surface and shift of inter pulse position in Crab pulsar. Adv. Astron. Space Phys. vol. 7, no. 1-2, pp. 30–35. DOI: https://doi.org/10.17721/2227-1481.7.30-3521. TROFYMENKO, S. V. and KONTOROVICH, V. M., 2017. Half-bare positron in the inner gap of a pulsar. Adv. Astron. Space Phys. vol. 7, no. 1-2, pp. 36–41. DOI: https://doi.org/10.17721/2227-1481.7.36-4122. KONTOROVICH, V. M. and TROFYMENKO, S. V., 2017. Radiation reflection from star surface reveals the mystery of interpulse shift and appearance of high frequency components in the Crab pulsar. In: International Conference Physics of Neutron Stars - 2017. 50 years after. 10–14 July 2017, St. Petersburg, Russian Federation. J. Phys.: Conf. Ser. Vol. 932. id. 012020. DOI: https://doi.org/10.1088/1742-6596/932/1/01202023. TYMCHENKO, M., GAVRIKOV, V. K., SPEVAK, I. S., KUZMENKO, A. A. and KATS, A.V., 2015. Quasi-resonant enhancement of a grazing diffracted wave and deep suppression of specular reflection on shallow metal gratings in terahertz. Appl. Phys. Lett. vol. 106, id. 261602. DOI: https://doi.org/10.1063/1.492341924. TRIBELSKY, M. I., 2012. Fano resonances in quantum and classical mechanics. Moscow, Russia: MIREA Publ. (in Russian).25. BESKIN, V. S., 2018. Radio pulsars – already fifty years! Phys. Usp. vol. 61, no. 4, pp. 353–380. DOI: https://doi.org/10.3367/UFNe.2017.10.03821626. YAKOVLEV, D. G., HAENSEL, P., BAYM, G. and PETHICK, C., 2013. L. D. Landau and the concept of neutron stars. Phys. Usp. vol. 56, no. 3, pp. 289–259. DOI: https://doi.org/10.3367/UFNe.0183.201303f.0307